2007
DOI: 10.1038/sj.sc.3102029
|View full text |Cite
|
Sign up to set email alerts
|

Topical phenytoin solution for treating pressure ulcers: a prospective, randomized, double-blind clinical trial

Abstract: Study design: Prospective, randomized, double-blind clinical trial. Objectives: To evaluate the efficacy of topical phenytoin solution in treating pressure ulcers among patients with spinal cord disorders and to evaluate the systemic absorption of topical phenytoin. Setting: Physical Medicine and Rehabilitation Unit, Christian Medical College, Vellore, India. Methods: Twenty-eight patients with stage 2 pressure ulcers were randomized to receive either phenytoin solution (5 mg/ml) or normal saline dressing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…It is noteworthy that studies of moderate to strong evidence pointed to the analgesic effects of this drug for wounds (10) , and their authors mentioned the use of phenytoin as a secure application (10,12,15) , important factors when one is concerned about systemic absorption that application of topical phenytoin may trigger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that studies of moderate to strong evidence pointed to the analgesic effects of this drug for wounds (10) , and their authors mentioned the use of phenytoin as a secure application (10,12,15) , important factors when one is concerned about systemic absorption that application of topical phenytoin may trigger.…”
Section: Discussionmentioning
confidence: 99%
“…Again it is important to consider that this drug was considered safe, inexpensive and effective in wound healing by several researchers considered in this integrative review (4,(8)(9)(10)(11)(12)(16)(17)19,21) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…Multiple methods of wound evaluation can be used to track an ulcer over time, including area, 27 volume, 28 linear growth of wound edges, 29 and the Pressure Ulcer Scale for Healing (PUSH) score. 30 Each of these methodologies has strengths and limitations that have led to varied use across clinical settings.…”
Section: Objective Wound Evaluationmentioning
confidence: 99%
“…10 While most of the studies regarding phenytoin and wound healing showed phenytoin efficacy there are studies which reported no important effect. [11][12][13] Several methods have been used to study healing promotion, but few studies investigated these modalities in comparison to each other. [14][15][16][17][18] In this study we evaluated the effect of low-level laser in wound healing and compared it with phenytoin.…”
mentioning
confidence: 99%